A Success Model for Semantic Technology based - Knowledge Management Systems: an Empirical Investigation - Babangida Umar, Abdulmajid; Ja’afar, Azmi; A. Jabar, Marzanah; Azrifah Azmi Murad, Masrah (International Journal of Engineering and Technology, 2018)
Provision of sufficient knowledge to users is the ultimate goal of a knowledge management system (KMS). Unfortunately, existing KMSâ€™s rely on human effort for access to desired knowledge. Semantic technologies have become a force for paradigm shift in KMS research. They aim to enable the delivery of the right knowledge to the right person and in the right context. Nevertheless, research gap exists on success models for the evaluation of semantic KMS. Most studies only focus on traditional KMS success. Hence, this paper proposes a model to predict the success of semantic KMS. The Relationship between two independent quality dimensions; knowledge and system quality, with two dependent constructs; perceived benefit and user satisfaction was examined through 5 formulated hypotheses. Using a survey method, questionnaires were administered to academicians in Malaysian public higher institutions. Out of a total 221 returned questionnaires, 199 valid responses were used for analysis. Contrary to the expectation, no direct relationship was found between knowledge quality, searchability, and user satisfaction. However, the result indicated that user satisfaction with semantic KM systems is positively associated with user perceived benefit of the system, which is strongly associated with the searchability of the system. Also, a weak association between knowledge quality and perceived benefit was revealed. Findings from the study highlights that, for success to be achieved, userâ€™s perception of benefit from the semantic KMS is key. This can be achieved if the system can provide adequate searchability and satisfactory quality of knowledge.Â Â Â